Wafer Hybrid Bonding을 위한 Upper wafer Handling 모듈 설계 및 제어 - 김태호; 문제욱; 최영만; 안다훈; 이학준 (반도체디스플레이기술학회지, 2022)
After introducing Hybrid Bonding technology into image sensors using stacked sensors and image processors, large quantity production became possible. As a result, it is currently used in most of the CMOS image market in smartphones and other image-based devices worldwide, and almost all stacked CIS manufacturing sites have focused on miniaturization using hybrid bonding. In this study, an upper wafer handling module for Wafer to Wafer Hybrid Bonding developed to increase the alignment and precision between wafers when wafer bonding. The module was divided two parts to reduce error of both the alignment and degree of precision during wafer bonding. Wafer handling module developed both new Tip/Tilt system controlling θx,θy of upper wafer and striker to push upper wafer. Based on this, it was confirmed through the stability evaluation that the upper wafer handling module can be controlled without any problem during W2W hybrid bonding.
Keywords: Tip/Tilt stage; Hybrid bonding; Piezo actuator; striker